A Membrane Topology Model for Human Interferon Inducible Transmembrane Protein 1 - Weston, Stuart (Public Library of Science, 2014)
InterFeron Inducible TransMembrane proteins 1–3 (IFITM1, IFITM2 and IFITM3) are a family of proteins capable of inhibiting the cellular entry of numerous human and animal viruses. IFITM1-3 are unique amongst the currently described viral restriction factors in their apparent ability to block viral entry. This restrictive property is dependant on the localisation of the proteins to plasma and endosomal membranes, which constitute the main portals of viral entry into cells. The topology of the IFITM proteins within cell membranes is an unresolved aspect of their biology. Here we present data from immunofluorescence microscopy, protease cleavage, biotin-labelling and immuno-electron microscopy assays, showing that human IFITM1 has a membrane topology in which the N-terminal domain resides in the cytoplasm, and the C-terminal domain is extracellular. Furthermore, we provide evidence that this topology is conserved for all of the human interferon-induced IFITM proteins. This model is consistent with that recently proposed for murine IFITM3, but differs from that proposed for murine IFITM1.